Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids

Fundamentals and sensing applications of 2D materials - Hywel, Morgan; Rout, Chandra Sekhar; Late, Dattatray J. (Elsevier, 2019)
Fundamentals and Sensing Applications of 2D Materials provides a comprehensive understanding of a wide range of 2D materials. Examples of fundamental topics include: defect and vacancy engineering, doping and advantages of 2D materials for sensing, 2D materials and composites for sensing, and 2D materials in biosystems. A wide range of applications are addressed, such as gas sensors based on 2D materials, electrochemical glucose sensors, biosensors (enzymatic and non-enzymatic), and printed, stretchable, wearable and flexible biosensors. Due to their sub-nanometer thickness, 2D materials have a high packing density, thus making them suitable for the fabrication of thin film based sensor devices.